Effect of gamma irradiation and ZnO nano particles on the A.C electrical conductivity of polyaniline - Mahmood, Hanaa Sh. Mahmood Sh. (Iraqi Journal of Physics, 2019)
Conducting polyaniline / ZnO nano composites are synthesized using a simplified cheap method with one step in –situ chemical polymerization, and AC conductivity (σac) of the prepared samples is studied in the range of frequency from 50 Hz to 15MHz.). The presence of polarons in the conjugated polymer chain are responsible for the ac conductivity is reliance on the frequency in these composites. The effect of increasing the ZnO nano particle concentration irradiation and gamma radiation on the electric conductivity was analyzed. The result showed that the nanocomposite prepared has the highest conductivity, from pure polyaniline and the exponential factor S was found increasing with ZnO content it was 0.739 for PANI pure and for 0.02 ZnO it was 1.415.